Penguatan Kapasitas Ekonomi Masyarakat Melalui Edukasi Pemasaran dan Inovasi Produk Susu di Desa Wisata Selo - Bogy Febriatmoko; Erisa Aprilia Wicaksari; Widya Prananta; Angga Pandu Wijaya (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Selo Village in Boyolali Regency is a center for dairy cattle farming and is also developing as a tourist village. However, most local residents still sell raw milk to middlemen without applying marketing strategies or product innovation. This community service activity aimed to provide education on the importance of dairy product marketing and to introduce innovative ideas based on local potential. The methods used included preliminary observation, open interviews, focus group discussions, interactive counseling, and evaluation through questionnaires and reflection. The activity involved 15 participants, including dairy farmers, homestay operators, café owners, and local youth. The results showed increased participant understanding of marketing strategies, tourism market opportunities, and the potential for milk processing. Most participants expressed interest in further training and began formulating product ideas such as yogurt, ice cream, and pasteurized milk. This program not only improved marketing literacy but also built motivation and collective awareness to develop independent businesses based on the village’s potential. Thus, the activity served as an initial step in promoting sustainable rural economic development.